Manajemen Pengelolaan Zakat Profesi di Rumah Zakat Cabang Banjarmasin - Jumi Herlita (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2016)
This study aims to determine how the management of zakat profession in Rumah Zakat (RZ) Banjarmasin. Zakat management is based on Law No. 23 of 2011 related to planning, organizing, actuating and controlling the collection, distribution and utilization of zakat, infaq, shodaqoh and wakaf. This research is qualitative research. The data collected through two stages of interviews and documentation. The results showed that the Rumah Zakat of Banjarmasin branch has well implemented the management of profession zakat through the number of zakat profession achievement of 2015 and 2016 is a product of charity that has been chosen by muzakki and also the largest contributor than other zakat product. The zakat distribution and utilization well implemented by programs submition to the professional members of RZ (MoR) in their respective fields.